Inhibiting Factors of the Implementation of 14 T in Pregnant Women at Puskesmas Padongko, District Barru - Risma, Alya (Golden Ratio of Data in Summary, 2021)
This study aims to determine the effect of inhibiting factors on the implementation of 14 T in pregnant women at Padongko Health Center in Barru District. This research is quantitative research through a descriptive-analytic approach with the research method of "Cross-sectional Study". This study used primary data through a survey of 175 respondents as a sample obtained from secondary data of 64 pregnant women. The survey was conducted from January 17 to February 31, 2016. Data were analyzed using statistical methods supported by the SPSS program. The results of this study indicate that: (1) service time has no significant effect on the implementation of 14T for pregnant women at the Padongko Health Center, Barru regency with a value of p = 0.108 greater than the significance value of α = 0.05: (2) the performance of midwives has a significant effect on the implementation of 14 T in pregnant women at the Padongko Health Center, Barru regency with a value of p = 0.002 less than the significance value of α = 0.05: (3) Husband's support has a significant effect on the implementation of 14 T in pregnant women at the Padongko Health Center, Barru regency with a p-value = 0.020 less than the significance value α = 0.05: (4) Mother's work has a significant effect on the implementation of 14 T in pregnant women at the Padongko Health Center, Barru regency with a value of p = 0.045 less than the significance value of α = 0.05: (5) recent education has no significant effect on the implementation of 14 T in pregnant women at the Padongko Health Center, Barru regency with a value of p = 0.071 is greater than the significance value of α = 0.05. So that the performance of midwives, husband's support, and mother's work influenced the implementation of 14T for pregnant women at the Padongko Health Center, Barru regency. However, of the three variables, the midwife's performance has a very significant effect on the implementation of 14 T at the Padongko Health Center, Barru regency.